Anti-Inflammatory Gel Preparation From Srikaya Leaf Extract (Annona Squamosa L.) In Male White Rats (Rattus Norvegicus) - Rugayyah Alyidrus; Reky Abbas; Nurfitria Junita; Ummu Kalsum T; Nur Laela Alydrus (International Journal Labs, 2025)
Soursop leaves (Annona squamosa L.) contain flavonoids whice work by inhibiting the cyclooxygenase enzyme whice occurs in inflammation, an anti-inflammatory drug agent whice works against the process of inflammation or onflammation, the body’s response to tissue damage caused by physical trauma, chemical substances and microbiology which can be characterized by redness, heat, pain, swelling. This study was conducted to determine whether the ethanol extract of soursop leaves (Annona squamosa L.) can be used as a gel preparation that is stable against chemical physics and to determine whether the gel preparation can provide anti inflammatory effects on male white rat (Rattus norvegicus). The method used in this study was a laboratory experiment, with soursop leaves extracted in the maseration method using 96% ethanol solvent, then formulated in a gel preparation with a concentration of 5 %, 6 %, 7 % follewed by evaluation of the organoleptic test preparation, pH, spreadability, viscosity or cycling test and anti inflammatory test using yhe 1 % carrageenan induction method using 15 rats. The results of the anti inflammatory test, the soursop leaf extract gela preparation in male white rats met teha stability of the gel preparation and the anti inflammatory test obtained a significant value (p>0.05) where at a concentration of 5 % it already had an anti inflammatory effect. Ethanol extract of soursop leaves can be made into a gel preparation that is physically and chemically stable and can provide anti inflamatory effectiveness in male shite mice.